Prevalence and associated factors of urinary tract anomalies in congenital heart disease - Ismail, Roziana (2017)
Urography following an angiocardiography has become a routine procedure in some centres. This has been done on the basis of the usage of contrast media during the procedure that are eliminated via the urinary system which makes the visualization of the urinary tract possible. The purpose of this study is to determine the prevalence of urinary tract anomaly (UTA) in patients with congenital heart disease (CHD) and the associated factors that contribute to the occurrence of UTA in these patients. This retrospective record review involved assessment of post angiocardiography urography images of CHD patients over a five-year period. A total of 244 patients were included in this study. Gender, maternal age at delivery, presence of associated syndrome or other extra-cardiac congenital anomaly, number of heart lesions, and type of CHD (acyanotic or cyanotic) were the factors studied. Multiple logistic regression is used to identify the independent factors associated with UTA in patients with CHD. The prevalence of UTA was 15.6%, whereby cyanotic CHD is the only predicted factor for the presence of UTA in CHD patient (adjusted OR 2.2, 95% CI 1.06, 4.63). As conclusion, the prevalence of UTA in CHD patients in this study is comparable to other studies. This high prevalence warrants a routine screening for UTA in CHD patients especially those with cyanotic type of CHD.